Acute static stretching with different volumes improves hamstring flexibility but not reactive strength index and leg stiffness in well-trained judo athletes - Kurtdere, I.; Kurt, C.; Nebioglu, I. Ö. (Journal of Human Sport & Exercise, 2021)
Purpose: The aim of this study was to compare the effects of different volumes of static stretching exercises (SS) on the reactive strength index (RSI), leg stiffness (Kleg), and hamstring flexibility in well-trained judo athletes. Method: In total, 17 international level judo athletes (11 women and 6 men; age, 20.47 ± 1.59 years; experience in judo, 11.35 ± 1.84 years) were recruited for this study. The athletes completed three different SS sessions named low (LV-SS: 3.5 min), moderate (MV-SS: 7 min), and high volumes (HV-SS: 10.5 min), 72 h apart, in a randomized crossover study. Before and after each SS exercise session, hamstring flexibility, RSI and Kleg were evaluated by a sit-and-reach test and a Myotest accelerometric system, respectively. Results: Different volumes of SS exercises improved hamstring flexibility (p < .05); however, no one exercise was superior in improving hamstring flexibility than the other (p > .05). Different volumes of SS exercises neither improved nor reduced RSI and Kleg (p > .05). Conclusion: Judo athletes can use LV-SS, MV-SS, or HV-SS for hamstring flexibility enhancement, and SS exercises can be used as a part of a warm-up session prior to judo training or competition.